2016
DOI: 10.1021/jacs.6b00142
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Efficient Formamidinium Tin Iodide Perovskite Solar Cells through SnF2–Pyrazine Complex

Abstract: To fabricate efficient formamidinium tin iodide (FASnI3) perovskite solar cells (PSCs), it is essential to deposit uniform and dense perovskite layers and reduce Sn(4+) content. Here we used solvent-engineering and nonsolvent dripping process with SnF2 as an inhibitor of Sn(4+). However, excess SnF2 induces phase separation on the surface of the perovskite film. In this work, we report the homogeneous dispersion of SnF2 via the formation of the SnF2-pyrazine complex. Consequently, we fabricated FASnI3 PSCs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
730
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 705 publications
(778 citation statements)
references
References 21 publications
19
730
1
4
Order By: Relevance
“…When the content of FA was enhanced, the grain boundaries gradually became more evident, and the FASnI 3 film shows crystal grains with sharp edges and clear boundaries. At lower FA contents ( x = 0.00, 0.25, and 0.50), some white grains are found in the films, which may be ascribed to the phase separation induced by SnF 2 19, 27. These films also exhibit incomplete coverage with a few pinholes, which may explain the low FF and the slightly lower average J sc of their corresponding devices.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…When the content of FA was enhanced, the grain boundaries gradually became more evident, and the FASnI 3 film shows crystal grains with sharp edges and clear boundaries. At lower FA contents ( x = 0.00, 0.25, and 0.50), some white grains are found in the films, which may be ascribed to the phase separation induced by SnF 2 19, 27. These films also exhibit incomplete coverage with a few pinholes, which may explain the low FF and the slightly lower average J sc of their corresponding devices.…”
Section: Resultsmentioning
confidence: 94%
“…The use of dimethyl sulfoxide (DMSO) as the precursor solvent has proven to be crucial in acquiring homogeneous films, as it forms a SnI 2 ·3DMSO intermediate phase that retards the rapid crystallization of Sn‐based perovskites 18. Seo and co‐workers employed a SnF 2 ‐pyrazine complex to improve the morphology of FASnI 3 films and obtained a PCE of 4.8% 19. There are also reports on adopting more suitable device structures for Sn‐based PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The author has concluded that the SnF 2 cannot only improve interfacial energy alignment but also increase stability to electron beam damage. Nowadays, most Sn‐based perovskites films prepared by solution deposition need additional SnF 2 to get good performance,47, 48, 57, 58, 73 including the recent (FA) 0.75 (MA) 0.25 SnI 3 based PSCs with the highest PCE of 8.12% 56. Additionally, Ma et al134 claimed that SnF 2 as the inhibitor of Sn 2+ oxidation in the MASnI 3 film could increase the fluorescence lifetime up to 10 times and give longer carrier diffusion lengths >500 nm, compared with pristine MASnI 3 films.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
“…In the case of tin perovskite, the popularly used SnF 2 additive for the elimination of the Sn vacancy could result in poor film morphology and bad device performance due to the phase separation of SnF 2 within the perovskite film 6, 135. In this regard, Lee et al58 introduced pyrazine into FASnI 3 perovskite precursors in conjunction with SnF 2 in the form of the SnF 2 ‐pyrazine complex ( Figure 10 a,b). The complex is believed to assist a uniform distribution SnF 2 in the perovskite film, thereby substantially improving the morphology of FASnI 3 perovskite.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 1 more Smart Citation